2015
DOI: 10.1152/ajpendo.00472.2014
|View full text |Cite
|
Sign up to set email alerts
|

Spermine oxidase maintains basal skeletal muscle gene expression and fiber size and is strongly repressed by conditions that cause skeletal muscle atrophy

Abstract: Skeletal muscle atrophy is a common and debilitating condition that remains poorly understood at the molecular level. To better understand the mechanisms of muscle atrophy, we used mouse models to search for a skeletal muscle protein that helps to maintain muscle mass and is specifically lost during muscle atrophy. We discovered that diverse causes of muscle atrophy (limb immobilization, fasting, muscle denervation, and aging) strongly reduced expression of the enzyme spermine oxidase. Importantly, a reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 51 publications
5
48
0
Order By: Relevance
“…To test whether a reduction in spermine oxidase expression is required for muscle atrophy, we transfected mouse muscle fibers in vivo with plasmid encoding spermine oxidase under control of a constitutively active promoter, and then, in the presence of constitutive spermine oxidase expression, we applied muscle atrophy stimuli (immobilization, p21 overexpression, fasting, or denervation). We found that forced expression of spermine oxidase reduced skeletal muscle fiber atrophy caused by immobilization, p21 overexpression, fasting, and denervation, indicating that a reduction in spermine oxidase expression is at least partially required for muscle atrophy during these conditions (8). Taken together, these data identified spermine oxidase as an important factor in the maintenance of skeletal muscle mass and a key downstream target of p21 during immobilization and other atrophy conditions.…”
Section: Insights Into Disuse Muscle Atrophy Using Systems Approachesmentioning
confidence: 59%
See 3 more Smart Citations
“…To test whether a reduction in spermine oxidase expression is required for muscle atrophy, we transfected mouse muscle fibers in vivo with plasmid encoding spermine oxidase under control of a constitutively active promoter, and then, in the presence of constitutive spermine oxidase expression, we applied muscle atrophy stimuli (immobilization, p21 overexpression, fasting, or denervation). We found that forced expression of spermine oxidase reduced skeletal muscle fiber atrophy caused by immobilization, p21 overexpression, fasting, and denervation, indicating that a reduction in spermine oxidase expression is at least partially required for muscle atrophy during these conditions (8). Taken together, these data identified spermine oxidase as an important factor in the maintenance of skeletal muscle mass and a key downstream target of p21 during immobilization and other atrophy conditions.…”
Section: Insights Into Disuse Muscle Atrophy Using Systems Approachesmentioning
confidence: 59%
“…To determine whether a reduction in spermine oxidase might be sufficient to induce muscle atrophy, we used in vivo RNAi to knoc kdown spermine oxidase expression in healthy, nonimmobilized, wild-type skeletal muscle fibers. We found that spermine oxidase knockdown decreased skeletal muscle fiber size, indicating that a reduction in spermine oxidase is sufficient to induce muscle fiber atrophy (8). To test whether a reduction in spermine oxidase expression is required for muscle atrophy, we transfected mouse muscle fibers in vivo with plasmid encoding spermine oxidase under control of a constitutively active promoter, and then, in the presence of constitutive spermine oxidase expression, we applied muscle atrophy stimuli (immobilization, p21 overexpression, fasting, or denervation).…”
Section: Insights Into Disuse Muscle Atrophy Using Systems Approachesmentioning
confidence: 76%
See 2 more Smart Citations
“…We also found that ablation of metallothioneins increased the mRNA levels of spermine oxidase (Smox). A role for Smox in maintaining basal skeletal muscle gene expression and fiber size has recently been described, and Smox is strongly repressed under muscle catabolic conditions such as fasting, immobilization, and denervation (36). In contrast, forced overexpression of Smox partially prevented muscle fiber …”
Section: Resultsmentioning
confidence: 99%